The impact of teamwork on missed nursing care - Kalisch, Beatrice J.; Lee, Kyung Hee (Nursing outlook, 2010)
Previous studies have shown that missed nursing care is a significant problem in acute care hospitals. Other studies have demonstrated that teamwork is a critical element in assuring patient safety and quality of care. The purpose of this study was to determine if the level of nursing teamwork impacts the extent and nature of missed nursing care. A sample of 2 216 nursing staff members on 50 acute care patient care units in 4 hospitals completed the Nursing Teamwork Survey and the MISSCARE Survey. The response rate was 59.7%. Controlling for occupation of staff members (eg, RN/LPN, NA) and staff characteristics (eg, education, shift worked, experience, etc), teamwork alone accounted for about 11% of missed nursing care. The results of this study show that the level of nursing teamwork impacts the nature and extent of missed nursing care. The study results point to a need to invest in methods of enhancing teamwork in these settings.